The Development of Multicultural Based Islamic Education Curriculum in General Higher Education - Sutardjo Atmowidjoyo; Mugiyono Mugiyono; Nahuda Nahuda (Ilomata International Journal of Social Science, 2022)
The development of Islamic Religious Education curriculum in Indonesian Public Universities is a necessity, because the nation which is undergoing changes in this era of democratization requires a framework of thinking and proper implementation for students. This is especially so when it is associated with the multiculturalism of this nation, both culture, ethnicity, language, and religion. The purpose of this research is mainly to get answers about how to develop a curriculum for Islamic religious education in public universities based on multiculturalism. Then this study also aims to obtain data on the implementation and development of teaching materials for Islamic religious education in public universities. The methods used in this research include: survey, exposed facto method, phenomenology related to developments that have been carried out by public universities and evaluating them. Thus, the qualitative and explanatory approaches are interrelated with each other. The results of this study are in the form of descriptions of Islamic religious education materials in public universities that have been developed over the last 3 years. In addition, the main material for PAI can be stated as a benchmark for MKDU in Indonesian universities.